Using sero-positivity to assess geospatial burden of contagious bovine pleuropneumonia on pastoral cattle herds of north-central Nigeria (2016)
Contagious bovine pleuropneumonia (CBPP) is an infectious disease of cattle endemic in sub-Saharan Africa. A cross-sectional sero-geospatial survey was conducted to assess the CBPP sero-geospatial burdens among estimate at-risk sero-positive cattle in nomadic and sedentary pastoral cattle production systems of north-central Nigeria, between January and August 2013. A total of 765 cattle in 125 nomadic herds and 375 cattle in 125 sedentary herds were sampled. Sera were analysed using c-ELISA. OpenEpi version 2.3 was used for statistical analyses. Geo-coordinates of herds were taken using Garmin GPS, while ArcGIS 9.3 was used to map geospatial data of sero-positive cattle and herds in the agro-geographical zones. In nomadic production, 16.2 % (95 % CI 13.7 to 19.0.) cattle were sero-positive in 47.2 % (95 % CI 38.2 to 56.3) herds. And the sedentary system had 9.6 % (95 % CI 6.9 to 12.0) sero-positive cattle in 27.2 % (95 % CI 19.6 to 35.9) herds. Agro-geographical zone A was more likely (OR 3.42; 95 % CI 1.90, 6.15) to have significant impacts on cattle-level sero-geospatial burden than Agro-geographical zone B. Also, Agro-geographical zone C was more likely (OR 5.14; 95 % CI 2.91, 9.08) to have significant impacts oncattle-level sero-geospatial burden than Agro-geographical zone B. The developed GIS CBPP risk maps showed various densities of its burdens in the agro-zones. The visualized proportional circle maps presented GIS usefulness in the active surveillance of CBPP, and if used in conjunction with sero-diagnosis, the maps would aid policymakers with practical imageries for livestock disease control decisions in pastoral cattle herds.